Value of minor trauma in the diagnosis of physical child abuse: 'The law of common man' - Vidanapathirana M; Gunethilake KMTB (Anuradhapura Clinical Society, 2015)
According to the definition of Meadow (1989), child abuse is defined as treating a child in an unacceptable way in a given culture at a given time. Major criteria for diagnosis of physical child abuse include sever, multiple, and patterned injuries with different stages of healing. Sometimes, even a single, minor injury may be sufficient to diagnose physical child abuse based on how much it is unacceptable to that particular culture at a given time. When single minor trauma is found, the criteria that could be used to decide whether it is unacceptable to the culture at a given time include; severe pain, severe disfiguration, negligence and lack of care such as injuries to main members of the body,unacceptable punishments such as biting, burning, pinching or tying to an object and,severe mental trauma such as due to non-sexual genital injuries. Much information can be gathered from minor injuries and their consequences such as how much of care was rendered. A new criterion to diagnose physical child abuse is introduced using single minor injuries. However, there is no objective and defined way of deciding how much the trauma is unacceptable for the culture at a given time. Therefore, this should be decided by law of common man, that is, if the ill-treatment of the child is unacceptable to a common man in the society.